Using Renewable Energy as an Innovation Source: Case Study of Pörtom Community - Bada, Hakeem Adeshina (My University, 2009)
The use of renewable energy as an alternative energy source cannot be overlooked at this present time of unstable price of fossil fuels combined with the recent economic crises. Renewable energy sources are available all over the world, but their availability greatly depends on their location. There are several technologies for exploiting renewable energy sources. These range from windmills to gigantic CHP power plants. Many communities are surrounded with renewable energy sources but lack the essential technologies for tapping them, and due to the price of the available ones, they are still avoided by every man. Consequently, the diffusion of renewable technology is exploited at low rate. In this research the use of renewable energy as an innovation source was tackled by looking at the meaning of innovation and how the two issues – renewable energy and innovation – integrate. New knowledge can come in different ways: it could be an improvement on the present technology or a completely novel innovative idea. However, what is new to some people might not be new to others. The use of renewable energy technologies varies and their use depends on the way the lead user uses these technologies. This study discovered how lead users’ experience is used to analyze their energy needs by simulating the available data in proposing the capacity of the CHP power plant and location of the power plant to the lead users.
Keywords: Renewable energy; Innovation; fi=Tuotantotalous|en=Industrial Management|